Legal Politics Legalization Convention In Perspective International Law - Mhd. Nasir Sitompul; Ariman Sitompul (LEGAL BRIEF, 2022)
Choice nomenclature Convention as a form of international agreement see the existence of the desire of countries that are bound by the agreement has a responsibility to implement and comply with the contents of the agreement because it is binding law post ratification and categorized as hard Law. Meanwhile, through analysis by using the concept of legalization seen that the form of legalization of the Geneva Convention is moderate where the level of obligation is high, the level of precision is high and the level the delegation is low. This means that although the responsibility of each country has been written with clear and detailed, but this agreement does not yet have a delegation of authority to third parties to implement, interpret, and apply regulations disputes; and also the possibility of creating new regulations. Without aspect third, the agreement tends to political aspects will be dominant over aspects law making it possible to be politicized even though the choice of legal form is hard law.